Coumarin‐4‐ylmethyl‐ and p‐Hydroxyphenacyl‐Based Photoacid Generators with High Solubility in Aqueous Media: Synthesis, Stability and Photolysis. Issue 3 (16th January 2020) - Adatia, Karishma K.; Halbritter, Thomas; Reinfelds, Matiss; Michele, Andre; Tran, Michael; Laschat, Sabine; Heckel, Alexander; Tovar, Günter E. M.; Southan, Alexander
Abstract: (Coumarin‐4‐yl)methyl (c4m) and p ‐hydroxyphenacyl ( p HP)‐based compounds are well known for their highly efficient photoreactions, but often show limited solubility in aqueous media. To circumvent this, we synthesized and characterized the two new c4m and p HP‐based photoacid generators (PAGs), 7‐[bis(carboxymethyl)amino]‐4‐(acetoxymethyl)coumarin (c4m‐ac) and p ‐hydroxyphenacyl‐2, 5, 8, 11‐tetraoxatridecan‐13‐oate ( p HP‐t), and determined their solubilities, stabilities and photolysis in aqueous media. The two compounds showed high solubilities in water of 2.77 mmol L −1 ±0.07 mmol L −1 (c4m‐ac) and 124.66 mmol L −1 ±2.1 mmol L −1 ( p HP‐t). In basic conditions at pH 9, solubility increased for c4m‐ac to 646.46 mmol L −1 ±0.63 mmol L −1, for p HP‐t it decreased to 34.68 mmol L −1 ±0.62 mmol L −1 . Photochemical properties of the two PAGs, such as the absorption maxima, the maximum molar absorption coefficients and the quantum yields, were found to be strongly pH‐dependent. Both PAGs showed high stabilities s24h ≥95 % in water for 24 h, but decreasing stability with increasing pH value due to hydrolysis. The present study contributes to a clearer insight into the synthesis, solubilities, stabilities, and photolysis of c4m and p HP‐based PAGs for further photochemical applications when high PAG concentrations are required, such as in polymeric foaming. Abstract : Clear as day : This work contributes to a clearer insight into the synthesis, characterization, solubility and stability of highly water‐soluble coumarin‐4‐ylmethyl‐ and p‐ hydroxyphenacyl‐based photoacid generators for further photochemical applications with high photoacid generator concentration requirements in aqueous media.